1996
DOI: 10.1200/jco.1996.14.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral breast tumor recurrence as a predictor of distant disease: implications for systemic therapy at the time of local relapse.

Abstract: It appears that early IBTR is a significant predictor for distant metastases. Whether early breast tumor relapse is a marker for or cause of distant metastases remains a controversial and unresolved issue. Implications for adjuvant systemic therapy at the time of breast relapse are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
0
7

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(104 citation statements)
references
References 17 publications
8
89
0
7
Order By: Relevance
“…The same applied to the conservation of histological type and features of equal or lesser differentiation. On the other hand, we confirmed the notion that early recurrences, that is occurring within the first 2 years, are associated with more deaths than late ones (Fourquet et al, 1989;Fisher et al, 1991;Whelan et al, 1994;Veronesi et al, 1995;Haffty et al, 1996;Fredriksson et al, 2002). In our study the group of patients with early recurrences had primary tumours significantly more proliferating and ipsilateral breast tumour recurrences with a higher degree of nuclear polymorphism than the group of patients with late recurrences.…”
Section: Discussionsupporting
confidence: 89%
“…The same applied to the conservation of histological type and features of equal or lesser differentiation. On the other hand, we confirmed the notion that early recurrences, that is occurring within the first 2 years, are associated with more deaths than late ones (Fourquet et al, 1989;Fisher et al, 1991;Whelan et al, 1994;Veronesi et al, 1995;Haffty et al, 1996;Fredriksson et al, 2002). In our study the group of patients with early recurrences had primary tumours significantly more proliferating and ipsilateral breast tumour recurrences with a higher degree of nuclear polymorphism than the group of patients with late recurrences.…”
Section: Discussionsupporting
confidence: 89%
“…3,10,22 Similar to the interval between mastectomy and chest wall recurrence, the interval between breast-conserving therapy and in-breast local recurrence has been shown to be a clinically significant prognostic factor. 23 With regard to survival, Whelan et al 24 found that a time to local recurrence of Ͻ 1 year was associated with a worse survival, whereas Doyle et al 10 found that a time to local recurrence of Ͻ 2 years and Haffty et al 25 found that a time to local recurrence of Ͻ 4 years was associated with worse survival. Patients with an early local recurrence are reported to subsequently develop distant metastases approximately 50% of the time.…”
Section: Survival After Mastectomy For In-breast Local Recurrencementioning
confidence: 99%
“…Short DFI was reported to be highly correlated with subsequent DM. 21,25,26,31,[41][42][43][44] These risk factors appear to reflect the inherent aggressive characteristics of primary tumors. 38,39 Thus the risk of developing DM would be predetermined before treatment, with local recurrence being a manifestation of this risk.…”
Section: Figurementioning
confidence: 99%